2019
DOI: 10.1038/s41598-018-36140-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibroblast activation and hyaluronan synthesis in response to hyperglycemia and diet-induced insulin resistance

Abstract: Diabetic patients are at a greater risk of heart failure due to diabetic cardiomyopathy and worsened outcome post-myocardial infarction. While the molecular mechanisms remain unclear, fibrosis and chronic inflammation are common characteristics of both conditions. Diabetes mellitus (types I and II) results in excessive hyaluronan (HA) deposition in vivo, and hyperglycemia stimulates HA synthesis for several cell types in vitro. HA-rich extracellular matrix contributes to fibrotic, hyperplastic and inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 60 publications
(67 reference statements)
3
14
0
Order By: Relevance
“…Under dynamic flow cultivation, ACTA2 expression remained unchanged. However, unchanged ACTA2 expression by HG is in line with our previous observations in VIC in a 2D culture model [16] and it is further in line with reports from other groups on VIC in a gelatin methacrylate 3D model [24] and also on cardiac fibroblasts [25]. Unaltered ACTA2 expression in our bioreactor system might therefore be indicative for a balanced stress level.…”
Section: Impact Of Diabetic Conditions On Degeneration Of Native Av Leafletssupporting
confidence: 92%
See 1 more Smart Citation
“…Under dynamic flow cultivation, ACTA2 expression remained unchanged. However, unchanged ACTA2 expression by HG is in line with our previous observations in VIC in a 2D culture model [16] and it is further in line with reports from other groups on VIC in a gelatin methacrylate 3D model [24] and also on cardiac fibroblasts [25]. Unaltered ACTA2 expression in our bioreactor system might therefore be indicative for a balanced stress level.…”
Section: Impact Of Diabetic Conditions On Degeneration Of Native Av Leafletssupporting
confidence: 92%
“…To our knowledge, the impact of diabetes or diabetic conditions on insulin signaling pathways in 2D or 3D models of CAVD has not been described in the literature so far. However, studies for classical insulin signaling have been reported for cardiac fibroblasts [25] and cardiomyocytes [37,38]. Binding of insulin to the insulin receptor triggers a phosphorylation cascade of downstream proteins, whereby the insulin signal is transmitted intracellularly [12].…”
Section: Insulin-dependent Signaling In Av Leaflet Tissuementioning
confidence: 99%
“…The greater role of insulinindependent glucose transport in cardiac and smooth muscle allows glucose uptake even when glycolysis and glycogenesis are impaired. The importance of insulin-insensitive glucose transport in development of diabetic retinopathy (Kumagai, 1999), atherosclerosis (Wall et al, 2018), diabetic nephropathy (Brosius and Heilig, 2005), pulmonary fibrosis (Cho et al, 2017), diabetic myocardial fibrosis (Asbun and Villarreal, 2006;Gorski et al, 2019) and non-alcoholic fatty liver disease (Nanji et al, 1995) has been demonstrated and is in support of our hypothesis that wooden breast shares substantial etiological factors with type 2 diabetes in mammals.…”
Section: Insulin-independent Glucose Transport In Chicken Skeletal Musupporting
confidence: 79%
“…The former is either mediated by angiotensin II activation or induced by high glucose and leptin via increasing transcription, secretion, and activation ( 169 , 262 , 263 ). On the other hand, in a study on a murine model of obesity and IR given a diabetogenic diet for 11 weeks, cardiac fibroblasts acquired enhanced myofibroblastic/fibrotic gene expression but reduced responsiveness to TGF-β1 ( 264 ). Similarly, cardiac fibroblasts isolated from db/db mice exhibited elevated collagen synthesis but weakened TGF-β1 response ( 256 ).…”
Section: Structural Changes In Diabetic Cardiomyopathymentioning
confidence: 99%